Risk Factors for Olfactory Dysfunction in Hospital Setting Following Covid-19 Infection Among Hospital Employees Following Treatment of Covid-19 Infected Patients: A Survey Research - Dolly Irfandy; Afriwardi Afriwardi; Bestari J. Budiman; Andani E. Putra; Dwitya Elvira; Claudia Triananda (LPPM Institut Pendidikan Nusantara Global, 2025)
Coronavirus disease 2019 (COVID-19) is an infectious respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To reveal the risk factors for olfactory dysfunction in employees with COVID-19 in the workplace of the subject hospital in Indonesia. This study was quantitative and descriptive, using data from questionnaires distributed to subject hospital in Indonesia employees who have experienced COVID-19. This study shows that anosmia (33.2%) is the most common olfactory dysfunction in COVID-19. COVID-19 infection often occurs in resident doctors (58.1%); women (55.6%); those aged 55 years (92.3%); those with comorbidities such as hypertension (4.3%) and obesity (65%); nonsmokers (91.5%) and smokers 10–20 cigarettes per day (5.1%); and nondrinkers (100%). Anosmia is the most common olfactory dysfunction in COVID-19. It is commonly experienced by resident doctors, women aged ≥55 years, employees without comorbidities, obese employees, nonsmokers, and nondrinker